PEMBERDAYAAN UMKM UNTUK MENINGKATKAN EKONOMI PASCA PANDEMI COVID-19 DI TUBAN - Anggraeny Puspaningtyas; Ahmad Adhi Suprayitno (REFORMASI, 2021)
The COVID-19 pandemic has had negative implications for the domestic economy such as decline in public consumption and purchasing power, decline in company performance, threats to the banking and financial sector, and the existence of MSMEs. On the corporate aspect, this pandemic has disrupted the performance of companies, especially those engaged in the trading sector. By looking at the current situation and not sure when the pandemic will end, local governments can help MSME actors by providing assistance according to the needs of each MSME actor. As is the case in Tuban Regency where MSME actors are required to be more sensitive and able to innovate quickly. This empowerment of MSME actors needs to be done, for the following three reasons. First, because the UMKM actors in Tuban Regency are suspected to still have not mastered the product marketing mechanism that is in accordance with market demands in the postmodern era as it is today. Second, because of the development of changes in consumer behavior that MSME actors need to understand so that they can produce products that are truly in accordance with the needs and desires of the market. Third, because the competitive climate for products produced by MSME actors tends to be more stringent, thus requiring breakthrough steps from MSME actors themselves to be able to take advantage of technology. Micro-enterprises and village governments need a survival strategy to maintain production and marketing stability. Therefore, an analysis related to community empowerment through MSMEs is needed to maintain economic stability after the Covid-19 pandemic in Tuban Regency.